Comparative study between dexmedetomidine and midazolam as pre-medication for the prevention of etomidate-induced myoclonus and attenuation of stress response at endotracheal intubation in laparoscopic cholecystectomies - Rathod, Sandesh; Maidul Haque; Patra, Sayak; Biswas, Chaitali (Asian Journal of Medical Sciences, 2024)
Background: Myoclonus is a common issue in etomidate anesthesia induction, and various drugs have been used to reduce its incidence, highlighting the ongoing search for better alternatives in anesthesiology. Aims and Objectives: The study analyzed the impact of dexmedetomidine (DEX) and midazolam pre-treatment on etomidate-induced myoclonus incidence, stress response at laryngoscopy, and intubation during etomidate induction. Materials and Methods: A prospective randomized controlled intervention study (superiority trial) was done involving 42 patients of age 20–60 years, randomly allocated in two equal groups (Group D: Inj. DEX was given as infusion (0.5 μg/kg) in 10 mL 0.9% normal saline over 10 min and 5 min before induction. Group M: Inj. Midazolam was given 0.02 mg/kg, prepared in 10 mL 0.9% normal saline, to be infused over 10 min and 5 min before induction). Myoclonus was graded after intravenous administration of etomidate (0.3 mg/kg) and hemodynamic response to laryngoscopy and intubation were observed at various time intervals. Statistical analysis was done using SPSS version 27.0. Independent t-test/Mann–Whitney test (for non-parametric data) and Chi-square test/Fisher’s exact test were used to compare variables. A P<0.05 was considered statistically significant. Results: The study found that DEX effectively suppressed stress response due to intubation compared to midazolam, with mean myoclonus gradation (Mean±SD) in Group-D and Group-M being 0.6190±0.7400 and 1.6667±0.8563, respectively, indicating a significant distribution with group. Conclusion: DEX was found to be more effective than midazolam in preventing etomidate-induced myoclonus and attenuating stress response compared to midazolam.